Interventions to promote exclusive breastfeeding among young mothers: a systematic review and meta-analysis - Christa Buckland; Debra Hector; Gregory S. Kolt; Paul Fahey; Amit Arora (BMC, 2020)
Abstract Background Exclusive breastfeeding rates in many high-income countries are considerably lower than the World Health Organization recommendations. Younger mothers are less likely than older mothers to exclusively breastfeed or to exclusively breastfeed for a long duration. This systematic review explores interventions to increase the rate of exclusive breastfeeding among young mothers in high-income countries. Methods A systematic search of the following databases was completed in August 2020: CINAHL, PubMed, MEDLINE, ProQuest, PsychInfo, Web of Science, Cochrane, Scopus and Embase. A manual search of the reference lists of all the included studies and published systematic reviews was also performed. The Cochrane Collaboration Risk of Bias Tool was used to assess the quality of the included studies. A random effects model meta-analyses was applied. Heterogeneity of outcomes between the studies was assessed using both the χ2 test and the I2 statistic. Results Of 955 records identified in the search, 392 duplicates were removed, and nine studies met the inclusion criteria. Seven studies were randomised controlled trial (RCTs) and two were quasi-experimental in design. Eight were conducted in the United States. The interventions included peer counselling, telephone support, massage, gift packs, financial incentive and antenatal education. Most studies included a combination of strategies, peer counselling being the most common. A meta-analysis of four of nine included studies did not detect a difference in rate of exclusive breastfeeding to 3 months postpartum (RR 1.44; 95% CI 0.82, 2.55; p = 0.204). This review is limited by the relatively few studies which met the inclusion criteria and the small sample sizes of most included studies. High rates of attrition and formula supplementation among the participants made it difficult to detect a statistically significant effect. Consistency in follow up times would enable more studies to be included in a meta-analysis. Conclusions Peer counselling was the most promising strategy associated with higher rates of exclusive breastfeeding. However, further studies are needed to understand the breastfeeding experiences of young mothers. Young mothers should be targeted specifically in intervention studies.